Caspian-type dinocysts in NE Turkey mark deep inland invasion of the Akchagylian brackish-water basin during the terminal Late Pliocene - Simakova, Alexandra N.; Tesakov, Alexey S.; Celik, Hasan; Frolov, Pavel D.; Shalaeva, Evgeniya A.; Sokolov, Sergey A.; Vasilieva, Maria A. (Pergamon-Elsevier Science Ltd, 2021)
The paper presents new data on brackish-water Upper Pliocene and Lower Pleistocene deposits that were studied in the Demirkent (Kars) and Pekecik (Erzurum) sections, NE Turkey. The Demirkent section is situated in the southwestern slope of the Shirak Late Cenozoic intermontane basin near the Turkish-Armenian border. The Pekecik section is situated to the SW of the Demirkent in the southwestern slope of the Horasan intermontane basin. Both sections are composed of clays, silts, and poorly cemented fine-grained sandstones and contain the brackish-water dinocysts of the Akchagylian type. The age of the deposits is determined by combined analysis of associations of molluscs and small mammals, palynological spectra, including dinocysts and algae, and magnetostratigraphic data. The Demirkent and Pekecik sections are dated to the Late Pliocene (Piacenzian). The maximum spread of the Akchagylian transgression influenced the inland areas of NE Turkey prior to the early Gelasian. The pollen spectra demonstrate progressive aridisation during sedimentation of the lower part of the Demirkent section and the wetter and cooler climate during sedimentation of the lower part of the Pekecik section. The analysis of brackish-water dinocysts and fresh-water algae in different beds of the Demirkent section indicates gradual freshening of the basin probably due to the sea level fall. In the Pekecik section, the brackishwater dinocysts are found in the lower part that is covered by the lignite-bearing layers without signs of marine influence. Recent altitudes of the Akchagylian brackish-water deposits give a possibility to estimate magnitudes and average rates of the Quaternary uplift of the western Lesser Caucasus. The elevation of the Upper Pliocene deposits of Demirkent and Pekecik sections shows the uplift rate of ca. 0.6-0.7 mm per year during 2.6 Ma.
Keywords: Late pliocene; Early pleistocene; Akchagylian transgression; Brackish-water dinocysts; Pollen spectra and diatoms; Molluscs and small mammals; Magnetic stratigraphy